ANALYSIS OF STUDENTS’ COURSEBOOK “THINK GLOBALLY ACT LOCALLY” APPLIED AT THIRD GRADE OF SMP NEGERI 9 AMBON BASED ON CUNNINGSWORTH’S CRITERIA - Solong, Alicia; Tupalessy, Pricilia; Afiliani, Afiliani; Hanayanti, Hanayanti (Pattimura Excellence Journal of Language and Culture, 2024)
One of the key components to assist the teacher and students’ teaching and learning activities in the classroom is the English coursebook. As a result, it is essential to select the appropriate course book to be used. Cunningsworth's criteria is one of several criteria that can be used to identify the appropriate course book. As a result, the objective of this research is to determine how relevant the English course book "Think Globally Act Locally" is for Third Grade students at SMP Negeri 9 Ambon according to the Cunningsworth's criteria. The course book's content was analyzed using descriptive qualitative research and the content analysis method by the researcher.